The In Situ Effect of Titanium Tetrafluoride Gel on Erosion/Abrasion Progression in Human Dentin - Mantilla,Taís Fonseca (2017)
Abstract Erosion incidence is increasing and its control is still a challenge in clinical practice. This study evaluated 4% TiF4-gel effects on eroded human dentin subjected to in situ erosive/abrasive episodes. Seventy-two previously eroded dentin slabs (0.05 M citric acid, pH 2.3, 20 min) were allocated to 6 groups (n=12) according to the treatment to be performed during the in situ phase and number of erosive/abrasive cycles, as follows: 4% TiF4-gel applied once (TiF41), twice (TiF42) or three times (TiF43) followed by 1, 2 and 3 erosive/abrasive cycles, respectively. Gel was applied before the beginning of the next cycle. Control groups were subjected to 1 (C1), 2 (C2) and 3 (C3) erosive/abrasive cycles only. A seventh group (n=12) comprised in vitro uneroded samples (UN) subjected to 3 erosive/abrasive cycles. Each cycle corresponded to 2 days of erosive (citric acid 0.5%, pH 2.6, 6x/day) and abrasive (electric toothbrush, 10 s/sample, 1 x/day) challenges. Samples were evaluated under profilometry and environmental scanning electron microscopy (ESEM). Atomic force microscopy images (AFM) were also made (n=3). Repeated measures 2-way ANOVA and Tukey test (p<0.001) showed that TiF42, which did not differ from TiF41 and TiF43, revealed a significant reduction in surface loss compared to all control groups. TiF41 and TiF43 showed no significant difference from C1, but both groups demonstrated significantly smaller surface loss than C2 and C3. ESEM and AFM micrographs suggested alterations on treated surfaces compared to samples from control groups, showing reduced diameters of dentinal tubules lumens. Therefore, TiF4 was able to reduce the progression of erosive/abrasive lesions.